Nutrition in Sportsmen - Banu B. Kalpakçıoğlu, (Archives of Rheumatology, 2008)
Everyday we are made aware of the need for proper preparation to maximize performance in sport, and this no longer applies only to the elite. In the 17th century the notion of nutrition and diet changed in European countries (Manz, 2001). First chemical experiments relied on the idea that salts resulted from a union of acids and bases, and digestion was no more regarded as a process of cooking but a succession of fermentations controlled by a balanced production of acids and alkali. Consequently, life seemed to depend on the equilibrium of acids and alkalis. In the 19th century food was systematically analyzed for the content of energy and macronutrients and the first scientifically based nutritional standards were then formulated. New methods to determine the concentration of nutritional elements promoted physiological and clinical research within acid-base metabolism after the 1950s. In this review basic answers to potential questions regarding the nutrition of sportsmen are given. (Rheumatism 2008; 23: 24-7)